Potensi Pengembangan Budidaya Pada Kawasan Konservasi Perairan Datok Bandar Kabupaten Lingga - Razai, Tengku Said; Ulfah, Fitria; Lestari, Febrianti; Apdillah, Dony; Karlina, Ita; Idris, Fadhliyah; Febrianto, Try (Universitas Riau, 2021)
The development of aquaculture in the Marine Protected Area (KKP) has to recognize the sustainability and the balancing of the ecosystem in that area. It causes limited rights of users who want to develop their business, where the issuance of permits and business management regulations is an obligation that must be followed by aquaculture business developers in the KKP area. The study aimed was to formulate the technical directions in developing the potential for aquaculture business in the Marine Protected Area of Datok Bandar (KKPD) at Lingga Regency. The method used in this research is a descriptive quantitative using analysis of the carrying capacity of the environment for aquaculture, water quality parameters, and a participatory approach. The results showed that the potential area to be developed for aquaculture was 3,736.01 ha. However, based on the carrying capacity analysis, only 268,420 ha or 7.2% from the existing potential can be utilized for aquaculture. Furthermore, based on the water quality measurements for aquaculture, the KKPD area was divided into 3 designations groups of aquaculture areas, namely the KJT, KJA, and seaweed. The number of aquaculture business units that were allowed in this area was 16,776 units consisting of 10,066 small business units and 6,710 medium business units with 7 types of superior fish. The limitation of land area and some business units in conservation areas were important to ensure the sustainability of the environment in the future. The implication of this research could be used as a basis for issuing aquaculture business permits, and to ensure that small-scale aquaculture fishermen have a large proportion. In addition to ensuring the existence of local communities who were generally small farmers, conservation areas were very vulnerable to environmental changes, so the risk factors and impacts of business utilization were important to consider.